Analisis Morfologi Afiksasi pada Novel Toon Dibalik Cadar Aisha Bab 19 Karya Almaira - Martha Amanda Sari; Alya Nadhifah Salsabila; Auralia Qurrota Aini; Taswirul Afkar (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The purpose of this study is to look at the morphology of affixation on vocabulary in Almaira's noveltoon ‘Behind Aisha's Veil’, especially in the third chapter with the theme ‘Love?’. The method used is qualitative. The data were collected through literature research and descriptive analysis that experienced affixation. This study found that the novel uses affixation, a linguistic process that involves adding affixes to the base form to produce new meanings. The study found that the use of affixes in the novel not only improves character descriptions but also increases the emotional depth of the story. The analysis results show that morphology plays an important role in shaping the meaning and characters in the story. It also shows that morphology reflects the social and cultural dynamics that women face in modern society. It is hoped that this research will enhance our understanding of how morphology is used in modern literary works.